The Ameliorative Role of Oregano aqueous extraction (Origanum vulgare) on Liver Enzymes, Hormones (Testosterone and Cortisol) and Antioxidant Parameters in Male Rats Exposed to Aluminum Oxide Nanoparticles - Jabbar Almiahy, Ashwaq; Jaber Hasan, Iman (Journal of Neonatal Surgery, 2025)
Aluminum oxide nanoparticles Al₂O₃-NPs are extensively applied in medicine, manufacturing and consumer products. However, their bioaccumulation- particularly in the liver - induces oxidative stress, and hepatocellular damage. Chronic exposure to Al₂O₃- NPs disrupts liver function, deteriorates testosterone synthesis and reduces antioxidant defenses. Oregano or (Origanum vulgare) , a Mediterranean herb exhibits potent antioxidant properties, anti-inflammatory and hepatoprotective features. Regardless evidence of its therapeutic interest, limited studies inspect its role in counteracting nanoparticle-induced toxicity. Forty adult male Norwegian rats are divided into four equal groups and treated orally as follows: G1: control (normal saline), G2: Al₂O₃ NPs (50 mg/kg/day), G3: Oregano aqueous extract (200 mg/kg/day) and G4: Combination the same doses of Al₂O₃ NPs + oregano extract . The experiment lasted for 30 days, animals were sacrificed after 24 hours from the last administration , blood samples were collected to study the biochemical parameters as well as the livers and testes were removed and preserved for histopathological examination. Results : levels of liver enzymes (ALT,AST and ALP), hormones (testosterone and cortisol) and antioxidant biomarkers (SOD), (GSH), (CAT) and (MDA) were improved by oregano aqueous extract in the combination group when compared to the same parameters in Al₂O₃-NPs group as well as its ameliorative role in the histopathological sections .In conclusion Oregano extract mitigates Al₂O₃- NP toxicity through antioxidant and anti-inflammatory mechanisms, supporting its use in nanoparticle-related toxicity management .